2005
DOI: 10.1175/jas3574.1
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence and Gravity Waves within an Upper-Level Front

Abstract: High-resolution dropwindsonde and in-flight measurements collected by a research aircraft during the Severe Clear-Air Turbulence Colliding with Aircraft Traffic (SCATCAT) experiment and simulations from numerical models are analyzed for a clear-air turbulence event associated with an intense upper-level jet/frontal system. Spectral, wavelet, and structure function analyses performed with the 25-Hz in situ data are used to investigate the relationship between gravity waves and turbulence. Mesoscale dynamics are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
103
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 62 publications
5
103
1
Order By: Relevance
“…This phenomenon has been identified repeatedly in both observational studies (Uccellini and Koch, 1987;Schneider, 1990;Fritts and Nastrom, 1992;Ramamurthy et al, 1993;Bosart et al, 1998;Koppel et al, 2000;Rauber et al, 2001; and numerical investigations of the observed cases (Powers and Reed, 1993;Pokrandt et al, 1996;Kaplan et al, 1997;Zhang and Koch, 2000;Zhang et al, 2001Zhang et al, , 2003Koch et al, 2001Koch et al, , 2005Lane et al, 2004). In addition, idealized simulations of dry baroclinic jet-front systems in a high-resolution mesoscale model have been performed to investigate the generation of mesoscale gravity waves (Zhang, 2004), the sensitivity of mesoscale gravity waves to the baroclinicity of jet-front systems (Wang and Zhang, 2007), and the source of gravity waves with multiple horizontal scales (Lin and Zhang, 2008).…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…This phenomenon has been identified repeatedly in both observational studies (Uccellini and Koch, 1987;Schneider, 1990;Fritts and Nastrom, 1992;Ramamurthy et al, 1993;Bosart et al, 1998;Koppel et al, 2000;Rauber et al, 2001; and numerical investigations of the observed cases (Powers and Reed, 1993;Pokrandt et al, 1996;Kaplan et al, 1997;Zhang and Koch, 2000;Zhang et al, 2001Zhang et al, , 2003Koch et al, 2001Koch et al, , 2005Lane et al, 2004). In addition, idealized simulations of dry baroclinic jet-front systems in a high-resolution mesoscale model have been performed to investigate the generation of mesoscale gravity waves (Zhang, 2004), the sensitivity of mesoscale gravity waves to the baroclinicity of jet-front systems (Wang and Zhang, 2007), and the source of gravity waves with multiple horizontal scales (Lin and Zhang, 2008).…”
Section: Introductionmentioning
confidence: 64%
“…Also, strong horizontal and vertical shear in the layer and the discontinuity in static stability at the tropopause provide a favorable environment to reflect, capture, break and dissipate gravity waves generated in the lower troposphere, such as those produced by surface fronts (Plougonven and Snyder, 2007). Gravity wave breaking and wave-induced turbulence (e.g., Koch et al, 2005) can contribute significantly to mixing of trace gases in the ExUTLS, thereby affecting chemical composition (Vaughan and Worthington, 2000). Also, convectively generated gravity waves may extend the impact of moist convection far above cloud tops through wave-induced mixing and transport (Lane et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The scaling behaviour, the wind shears and jet stream characteristics on such targeted flights were indistinguishable from those on the three ferry flights HonoluluAnchorage-Long Beach-Honolulu. More detailed information can be found in Hovde et al (2009), in Ray et al (2004 and in Koch et al (2005). The Winter Storms 2004 data analysed here involved 10 aircraft flights over a roughly 2 week period over the northern Pacific each dropping 20-30 drop sondes.…”
mentioning
confidence: 99%
“…The transport of trace gas species may be reversible or irreversible, depending on processes occurring on different scales. Irreversible mixing is promoted by turbulence induced, for example, by nonlinear wave interaction, wave breaking, or dissipation Whiteway et al, 2003;Koch et al, 2005;Lane and Sharman, 2006). Danielsen et al (1991) showed that waves with large horizontal wavelengths (∼ 36-270 km) and enhanced vertical amplitudes are significant carriers of energy, momentum and trace species.…”
Section: R Heller Et Al: Mountain Waves Modulate the Water Vapor DImentioning
confidence: 99%